American cinema impact on the formation, reflection and dissemination of national stereotypes (Халықаралық қатынастар және халықаралық құқық сериясы, 2022)
In the current age of widespread mass culture, cinema, as its most popular and widespread medium, is a rich source of information. In a world of rapidly developing technologies and a high pace of life, when the printed word, unfortunately, fades into the background, cinema acquires a special role in shaping the worldview of entire generations. Reality in art culture is the most important ideological problem. The version of reality in the "big staging of life" - in particular, on the screen - determines both our attitude to reality and this reality itself. Our whole life is stereotyped, and whatever the attitude to stereotypes, they have become a criterion for an individual's assessment of the surrounding reality and judgments about his own and other peoples. Cinema, which is an expression of the most common and widespread stereotypes, is an example of the practical application of stereotypical thinking. Hollywood plays a huge role in portraying different races and different cultures by virtue of their movies. In this regard, in the current article the author analyzes the means of formation of national stereotypes. The main focus of this study is Hollywood as an instrument for the stereotypes dissemination and reflection all over the world in simple movies. By means of a thorough analysis and practical research (survey and interview), the author reveals whether stereotypes do really correspond to the realities they show in the movies and if different nationalities/ethnicities are satisfied with their depiction in the American movies that are incredibly popular all over the world. In the end, there are some advisory and recommendary assumptions for the people not to be exposed to the superficial images they see in the movies because it may impede them from successful international relations.Keywords: stereotypes, Hollywood, soft power, American cinema, racism, prejudice, international image, national representation, national depiction, discrimination, Asian stereotypes, Black people stereotypes, Muslim stereotypes.